2016
DOI: 10.1093/nar/gkw857
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Research Database: An integrated bioinformatics resource for influenza virus research

Abstract: The Influenza Research Database (IRD) is a U.S. National Institute of Allergy and Infectious Diseases (NIAID)-sponsored Bioinformatics Resource Center dedicated to providing bioinformatics support for influenza virus research. IRD facilitates the research and development of vaccines, diagnostics and therapeutics against influenza virus by providing a comprehensive collection of influenza-related data integrated from various sources, a growing suite of analysis and visualization tools for data mining and hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
266
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 312 publications
(278 citation statements)
references
References 25 publications
2
266
0
Order By: Relevance
“…The inferred phylogenetic trees were used to classify H1N1 and H1N2 sequences into previously defined genetic clades: H1‐α, H1‐β, H1‐γ, H1‐γ2, H1pdm09, H1‐ δ1, and H1‐ δ2 . These clades correspond to a recently released a global nomenclature for H1 HA genes from swine IAV . The clade designations are as follows: 1A.1 and 1A.1.1 (H1‐α), 1A.2 (H1‐β), 1A.3.3.3 (H1‐γ), 1A.3.2 (H1‐γ2), 1A.3.3.2 (H1pdm09), 1B.2.2 (H1‐δ1), 1B.2.2.1 (H1‐δ1a), 1B.2.2.2 (H1‐δ1b), and 1B.2.1 (H1‐ δ2).…”
Section: Methodsmentioning
confidence: 99%
“…The inferred phylogenetic trees were used to classify H1N1 and H1N2 sequences into previously defined genetic clades: H1‐α, H1‐β, H1‐γ, H1‐γ2, H1pdm09, H1‐ δ1, and H1‐ δ2 . These clades correspond to a recently released a global nomenclature for H1 HA genes from swine IAV . The clade designations are as follows: 1A.1 and 1A.1.1 (H1‐α), 1A.2 (H1‐β), 1A.3.3.3 (H1‐γ), 1A.3.2 (H1‐γ2), 1A.3.3.2 (H1pdm09), 1B.2.2 (H1‐δ1), 1B.2.2.1 (H1‐δ1a), 1B.2.2.2 (H1‐δ1b), and 1B.2.1 (H1‐ δ2).…”
Section: Methodsmentioning
confidence: 99%
“…To date, it has been applied successfully to classification of avian HA/H5 sequences, according to the nomenclature of the WHO/OIE/FAO H5N1 Working Group (29), to distinguishing new pandemic 2009 H1 viruses from earlier seasonal H1 viruses in humans and other hosts, and to classifying U.S. swine H1 HA phylogenetic clades. These three applications have been implemented on IRD (30, 31). …”
Section: Methodsmentioning
confidence: 99%
“…Classification by this web-based tool matched expertly curated, manual classification of the sequences >99% of the time. This tool will be released on the Influenza Research Database (IRD) at http://www.fludb.org (30, 31) to facilitate the adoption of the unified nomenclature.…”
Section: Introductionmentioning
confidence: 99%
“…Among the H4 HA sequences detected worldwide, publicly available in the Influenza Research Database, the majority were identified in avian species (2140/2235), a small number were found in mammals (5 in swine, 3 in sea mammals, and 2 in muskrats), 84 were detected in environmental samples and one was of unknown origin (Zhang et al, 2017). Pigs were experimentally challenged with 5 avian H4 strains from ducks in a comprehensive study that assessed the susceptibility of swine to 38 avian IAV strains (Kida et al, 1994).…”
Section: Introductionmentioning
confidence: 99%